Two new species of Hyalojassini (Hemiptera: Cicadellidae: Iassinae) to the genera Comanopa Blocker and Gehundra Blocker, description of the male of G. sordida (Baker) and key to species - Domahovski, Alexandre C. (European Journal of Taxonomy, 2021)
Comanopa Blocker, 1979 and Gehundra Blocker, 1976 are small and poorly known genera of leafhoppers, previously comprising four and five species, respectively. In this study, two new species are proposed: Comanopa mananciensis sp. nov. from the state of Paraná, Southern Brazil, and Gehundra cristalinensis sp. nov. from the state of Mato Grosso, Centralwestern Brazil. The male of Gehundra sordida (Baker, 1900) is studied by the first time. Detailed descriptions and illustrations of males and females are provided and keys to males of Comanopa and Gehundra are given.